Quiet Quitting in Times of Uncertainty: Definition and Relationship With Perceived Control. - Hervé, Justine; Oh, Hyewon (Human Resource Management)
Uncertain times—such as periods of political turmoil, economic instability, health, or climate crises—can diminish individuals' perception of control over their environment. This paper hypothesizes that reduced perceptions of control may impact how individuals relate to their work, specifically, triggering quiet quitting, where employees intentionally refrain from tasks beyond their job requirements. Evidence supports this hypothesis: for example, the phenomenon of quiet quitting has resurged in the post‐pandemic era, coinciding with a significant decline in workers' perceived control around that time. However, no research has yet explored the relationship between perceived control and quiet quitting. Drawing on motivation theory, this paper posits that workers' perceived control, reflected in their beliefs about the effort‐reward link, can explain quiet quitting. To test this, we conducted two extensive online surveys with two main objectives: first, to conceptually refine and operationalize the construct of quiet quitting with a 5‐item scale; second, to examine the relationship between perceived control and quiet quitting. Our findings reveal a significant negative association between workers' perceived control and their propensity to engage in quiet quitting. This relationship is partially mediated by a reduced affective commitment to the employer and an elevated sense of replaceability. A direct implication of our results is that initiatives aimed at restoring workers' sense of agency at work might reduce quiet quitting behaviors.